Potential impacts of national absorptive capacity in internet of things to socio-economic aspects in some countries and lessons for Vietnam - Sinh, Bach Tan; Duong, Duong Khanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
From study of experience of some countries in determination of potential impacts of national absorptive capacity in Internet of Things (IoT) to socio-economic aspects, particularly to contributions to national GDP growth, as well as some international studies on the nature of national absorptive capacity and the linkage between this capacity and the extent of socio-economic impacts and its spillover effects, the paper will present the proposal of the research team on the project of analysis frame of national absorptive capacity in IoT of Vietnam in compatibility to socio-economic development and particularly in context of transition of economic structure to market mechanisms and international integration. Also, the paper provides some initial recommendations for policies to enhance the national absorptive capacity in IoT of Vietnam. Code: 18121401